Analisis Elemen Bauran Pemasaran Yang Mempengaruhi Loyalitas Pelanggan Rumah Sakit: Systematic Review - Agustine, Elisabeth Dewi (UI Scholars Hub, 2017)
Increasing the number of hospitals improves the competitive of medical services. Hospitals must have the right marketing strategy to retain old customers and attract new customers. To increase of the hospital customer loyalty, the marketing mix can be use as tool. Aim: To know the marketing mix elements that influence the loyalty of hospital customers. Preferred report items for systematic reviews and meta-analyzes (PRISMA) are evidence based methods for performing systematic reviews. There are 33.33% of the 9 studies that mention 7 elements (product, price, place, people, process, physical evidence, promotion) in the marketing mix, all of which affect the loyalty of hospital patients. The physical evidence influences the patient's loyalty to the hospital, where physical evidence has a dominant influence in 33.33% of the study. Five among of nine studies founded elements of the marketing mix that did not affect customer loyalty. The prices and promotion elements occupied the lowest percentage of 20%. It showed that the price and promotion elements can influence loyalty more than products, officers, processes and places. Not all 7-element of marketing mixes can influence the loyalty of patients, it’s depends on the internal and external circumstances of the hospital. Continuousing evaluation, communication and coordination are expected to be effective in the hospital marketing program.